Halobacillus trueperi CT7: A spore-forming, gelatinase producing, salt-tolerant bacteria isolated from Çankırı Salt Mine - KESBİÇ, Fevziye Işıl; GÜLTEPE, Nejdet; TÜZEMEN, Naci (Kastamonu University, 2023)
Halophilic microorganisms are an extreme group of organisms that can spread at high salt concentrations, and a significant part of them consists of halophilic bacteria. Salt mines are important sources where halophilic bacteria are detected. In this study, Halobacillus trueperi CT7, a halophilic bacterium, was isolated from Çankırı Salt Mine. It was determined that this strain obtained showed 98.16 % similarity to Halobacillus trueperi by DNA isolation and sequence analysis as well as biochemical analysis. In addition, two-dimensional (scanning electron microscopy) and three-dimensional (atomic force microscopy) images of Halobacillus trueperi were performed. In order to determine the industrial use potential of the microorganism, the minimum and maximum salt concentrations, temperature and pH ranges, as well as the enzyme activities, where the species can grow, were determined qualitatively. The interest in halophilic organisms for their use in extreme industrial processes is increasing day by day. It is thought that this study will contribute to future studies on halophilic bacteria.
Keywords: Halophilic bacteria; Halobacillus trueperi; Salt Mine; Biyomateryaller; Biomaterial; 6. Clean water